Inhibition of UV-C light-induced apoptosis in liver cells by 2,3,7,8-tetrachlorodibenzo-p-dioxin - Chopra, M.; Dharmarajan, Arunasalam; Meiss, G.; Schrenk, D. (2009)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a highly toxic pollutant ubiquitously present in the environment. Most of the toxic effects of TCDD are believed to be mediated by high-affinity binding to the aryl hydrocarbon receptor (AhR) and subsequent effects on gene transcription. TCDD causes cancer in multiple tissues in different animal species and is classified as a class 1 human carcinogen. In initiation-promotion studies TCDD was shown to be a potent liver tumor promotor. Among other theories it has been hypothesized that TCDD acts as a tumor promotor by preventing initiated cells from undergoing apoptosis. We examined the effects of TCDD on ultraviolet C (UV-C) light-induced apoptosis in primary rat hepatocytes and Huh-7 human hepatoma cells. TCDD inhibits UV-C light-induced apoptosis in both cell types. This effect is seen with chromatin condensation and fragmentation and appears to be mediated by the AhR in rat hepatocytes. Apoptosis induced by UV-C light in these cells is caspase-dependent and is accompanied by alterations in apoptosis-related gene expression such as up-regulation of proapoptotic bcl-2 family genes like bak and bax, and a marked down regulation of the expression of the antiapoptotic bcl-2. TCDD treatment of irradiated hepatocytes induces the expression of some apoptosis-related genes (birc3, dad1, pycard, tnf). Upstream apoptotic events, namely caspase activation and caspase substrate cleavage are not inhibited by TCDD treatment. We hypothesize that TCDD inhibits late-stage apoptotic events that lead to internucleosomal DNA fragmentation, maintaining chromosomal integrity probably in order to sustain metabolic capacity and hepatic elimination of substrates despite of an initiation of apoptosis. © The Author 2009. Published by Oxford University Press on behalf of the Society of Toxicology. All rights reserved.